The effect of a silicone swim cap on swimming performance in tropical conditions in pre-adolescents - Hue, O.; Galy, O. (Journal of Sports Science & Medicine, 2012)
We tested whether the silicone swim caps (SC) worn by young swimmers in a tropical climate negatively influence aerobic performance. Nine trained pre- adolescents [11.8 (± 0.8) years] swam randomized 800-m trials (water: 32.9°C, outdoors: shade, 29.2± 0.2 °C, 74 ± 0.3 % rh) with a SC or a nude head (NH). Performance times and heart rate (HR) were monitored continuously. Rectal temperature (Trec) was measured before and after trials. The rating of perceived exertion (RPE) was assessed. Stroke frequency (SF), stroke length (SL) and stroke index (SI) were measured every 50-m. The SC trial was significantly longer than NH (799 ± 16 and 781 ± 16 seconds, respectively). Mean delta Trec was significantly greater in SC (0.2 ± 0.1°C vs. -0.1 ± 0.1°C in SC vs. NH), mean SI was significantly different in SC versus NH (1.83 ± 0.07 vs 1.73 ± 0.06); but RPE and mean HR, SF and SL showed no change. We conclude that a silicone swim cap worn in tropical environment significantly decreased 800-m crawl performance without affecting HR or RPE. Silicone swim caps worn by young swimmers in a tropical environment may also have negative effects on training capacity.